Thermal Diffusivity Measurement of La Doped SrSn0 3(Sr1_xLaxSn03 ) Ceramics by Photoflash Method - Liew, Josephine Ying Chyi; Mat Yunus, W. Mahmood; Ahmad Taha, Iftetan; Shaari, Abdul Halim (Universiti Putra Malaysia Press, 2005)
Thermal diffusivity, a of a medium is the thermophysicaJ property which determines the speed of heat propagation by conduction during changes of temperature with time. The measurement of thermal diffusivity can be carried out at room temperature by photoflash method, which employs a high intensity camera flash as the excitation source. In this paper, Sr1 _ xLaxSn0 3 ceramics doped with different compositions of La (x = 0.1, 0.4, 0.6, 0.8, 1.0) was investigated for their thermal diffusivity. The thermal diffusivity values varied from 0.44 x 10-2 - 1.15 X 10-2 cm2/s corresponding to x = 0.1 to x = 1.0. The morphology and structure of Sr1 _xLaxSn03 ceramics were analysed from SEM and XRD measurements to support the thermal diffusivity behaviour.